A Study on the stereotype formation in the University of the Philippines, Diliman and its effects on the students' attitude, interaction patterns and communication behavior - Cuanias, Katrina Genevieve N.
The subject of this study is the stereotype formation of UP students on other UP students and the effects of stereotyping on their attitude, interaction and communication patterns. Because a number of studies already were made on the stereotypes that people not from UP hold on UP students, the researcher decided to conduct one that would focus on UP students and what they think of their schoolmates and what attitudes they hold and how they act around them. Theories and books on social interaction proved to be useful to the researcher. Among which are the Theory of Symbolic Interactionism and the Social Judgement Theory. The said theories, and more, provided the researcher with the necessary information she needed for her framework. Several theses also were referred to as some studies on the perception of other students on UP students already were done. The study made use of the survey and Focus Interviews to gather data. The respondents were students from the different colleges of the Diliman Campus of the University. There were a total of 149 respondents and 8 informants, also from different colleges. From the study, it was seen that UP students have a positive perception of other UP students and that their attitude towards other UP students is generally positive. The study also made evident what categories UP students use when labeling others. The more frequently used categories was that of intelligence, the students' manner of dressing and behaving in public, the college where they belong, their economic status and political behavior. The labels that came up were that of "cono" or students that are rich or those that belong to colleges of Business Administration and Economics and Engineering students which were described as students who are good in Mathematics. The respondents also mentioned their friends and classmates as their sources of information regarding labels they have and that these people influence them by telling the respondents certain labels and stereotypes that they hold. Which is then held by the respondents as their own. It was also seen that stereotyping does have an effect on the attitude, interaction and communication behavior that UP students have on other UP students. It was revealed in the study that the respondents' attitude, interaction and communication behavior differ depending on the stereotype they are with. That they wouldn't initiate contact with students whom they have stereotyped as someone better than them. These despite the majority's opinion that they are neither inferior nor superior compared with other UP students. The study was focused on the perception and opinion of undergraduate students of the University. Further studies are therefore recommended, this time focusing on students taking up graduate studies in the University as they may hold creation traits or opinion that greatly differs from that of undergraduate students.